1998
DOI: 10.1001/archinte.158.18.2054
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Mortality After Myocardial Infarction

Abstract: Background: Studies of sex differences in mortality after myocardial infarction (MI) have shown conflicting results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
3
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(100 citation statements)
references
References 53 publications
8
88
3
1
Order By: Relevance
“…Several studies have indicated that shortand long-term post-MI (Koek et al 2006;Milcent et al 2007) and post-stroke mortality is higher in women than in men (Appelros et al 2009;Lewsey et al 2009;Appelros et al 2010;Andersen et al 2011). Some studies found that the female disadvantage in post-stroke survival was limited to younger ages (Vaccarino et al 1998(Vaccarino et al , 1999(Vaccarino et al , 2001Nielsen et al 2014), while others found that rates of post-MI and post-stroke survival did not differ significantly by gender after the baseline and clinical characteristics were taken into account (Galatius et al 1996;Herman et al 1997;MacIntyre et al 2001;Di Carlo et al 2003;Isaksson et al 2011;Olsen et al 2012).…”
Section: Sex Differences In Morbiditymentioning
confidence: 99%
“…Several studies have indicated that shortand long-term post-MI (Koek et al 2006;Milcent et al 2007) and post-stroke mortality is higher in women than in men (Appelros et al 2009;Lewsey et al 2009;Appelros et al 2010;Andersen et al 2011). Some studies found that the female disadvantage in post-stroke survival was limited to younger ages (Vaccarino et al 1998(Vaccarino et al , 1999(Vaccarino et al , 2001Nielsen et al 2014), while others found that rates of post-MI and post-stroke survival did not differ significantly by gender after the baseline and clinical characteristics were taken into account (Galatius et al 1996;Herman et al 1997;MacIntyre et al 2001;Di Carlo et al 2003;Isaksson et al 2011;Olsen et al 2012).…”
Section: Sex Differences In Morbiditymentioning
confidence: 99%
“…Resultados -A letalidade hospitalar do IAM foi mais alta em mulheres (19,5% vs 9,4%) do que em homens (odds ratio (OR)= 2,34; IC 95%= 1,12-4,47 Embora diversos estudos mostrem, de forma consistente, maior mortalidade em mulheres do que em homens com IAM, as razões para esse fenômeno não estão devidamente esclarecidas [1][2][3][4][5][6][7][8][9][10] . Estudos conduzidos fora do Brasil, no entanto, sugerem que a idade mais avançada, a maior gravidade da insuficiência ventricular esquerda (IVE) e fatores relacionados com à terapêutica, podem, em conjunto, contribuir para a maior letalidade do IAM entre as mulheres.…”
Section: Métodos -Estudo De Coorte Retrospectivo Envolvendo 388 Paciunclassified
“…These studies have consistently shown that women are, on average, 10 years older at presentation; have a higher burden of comorbidities; and are less likely to receive up‐to‐date treatment, including reperfusion therapy, than men 7. Accounting for age differences often attenuates the observed sex differences in all‐cause mortality, suggesting that age‐associated comorbidity accounts for the excess risk in women 2, 3…”
Section: Introductionmentioning
confidence: 98%
“…Studies have identified that women have higher all‐cause mortality than men following acute myocardial infarction (AMI) 1, 2, 3, 4, 5, 6. These studies have consistently shown that women are, on average, 10 years older at presentation; have a higher burden of comorbidities; and are less likely to receive up‐to‐date treatment, including reperfusion therapy, than men 7.…”
Section: Introductionmentioning
confidence: 99%